(untitled) (Research, Society and Development, 2020)
Introduction: Injuries or any other health problems with sudden onset, generated by violence or other exogenous cause, are called external causes (EC). The indicator Potential Years of Life Lost - PYLL expresses the impact of early deaths in relation to the life expectancy for a given population. ECs were the major causes of death in children aged 1 to 9 years with 1,037 deaths (19.38%). Objective: To determine PYLL by EC among children aged 1 to 9 years in the state of Piauí, Brazil. Methods: This is a retrospective, longitudinal study with a quantitative approach. Its scenario is the State of Piauí. The population and sample were composed of deaths from EC registered in the Mortality Information System - MIS from Brazil, which occurred in children in the intended age group. For data analysis, the method that establishes a limit age for the calculation of PYLL was used, based on the average life of the population. Results: In Piauí between January 2000 and December 2018, there were 1,037 deaths (11.67%). The highest number of PYLL was found among male children, aged 5 to 9 years. Deaths caused by drowning were predominant, with 258 deaths (24.9%), being responsible for 16,857 PYLL, followed by accidents with pedestrians, with 184 deaths (17.8%), adding up to 11,911.5 years. Conclusion: Accidental drowning and submersion and pedestrian accidents predominate as the main EC. It can be estimated that 67,581 years of life for children aged 1 to 9 years were lost by EC in Piauí.